Conspiracy Theories, Messianic Populism and Everyday Social Media Use in Contemporary Brazil: a Glocal Semiotic Perspective (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Scholars have highlighted the bond between digital populism and conspiracy theories. They have also shown that conspiracy theories from around the globe rely on similar narrative patterns, as well as that being locally adapted. This paper adds to this body of research by exploring the glocal dimension of populist conspiracy theories in the contemporary Brazilian political context. Using a semiotic approach to glocalization, I tackle one recurrent motif of global conspiracy theories: the domination of the elites over the people, which contributed to the election of Jair Bolsonaro in 2018, as well as to the rise of his approval rating in 2019 and 2020. I argue that this particular narrative feature has taken on, in Bolsonaro’s case, shapes and tones which are directly related to the local religious semiosphere, especially the Neo-Pentecostal evangelical messianism: indeed, the image of Bolsonaro as a national messiah is characterized by a high rate of mysticism, eschatology and aesthesic load, which are three of the main distinctive traits in Brazilian evangelicalism. Moreover, I discuss the role of everyday social media use in this glocal meaning-making process. I show how on Bolsonarist public WhatsApp groups, everyday banalities, global and local populist, conspiracy and religious narratives were mixed in a way that fostered the image of Bolsonaro as a martyr and a political messiah anointed by the Lord.
Keywords: glocalization; conspiracy theories; digital populism; messianism; Brazil